Netralitas Majelis Kehormatan Hakim Konstitusi dalam Menegakkan Kode Etik Hakim: Kajian Perbandingan dengan Komisi Yudisial - Rasji; Namira Diffany Nuzan; Putri Meilika Nadilatasya; Sherley Lie (CV Rewang Rencang, 2024)
The Indonesian state is a state of law that actually prioritizes law over politics. The Indonesian state in regulating the structure of the state administration and the actions of its people always prioritizes the laws that have been compiled and made by the government and must also be implemented. In its implementation, the State of Indonesia has set up a judicial institution which specializes in overseeing the code of ethics of a Judge who will decide the case, namely the Judicial Commission. The purpose of this study is to determine the neutrality of an independent institution, namely the Honorary Council of the Constitutional Court in carrying out its duties using a research method approach to legislation or pre-existing literature. In the discussion of this paper, several new facts were found regarding the supervision carried out by the Judicial Commission as a judicial supervisory institution that only supervises Supreme Court Judges but does not supervise Constitutional Judges. Indeed, if the Constitution conducts direct supervision of Constitutional Judges, it will certainly lead to non-neutrality in the implementation of such supervision.